2019
DOI: 10.1101/803452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-specific causal disease effect sizes in functionally important regions impacted by selection

Abstract: 30Many diseases and complex traits exhibit population-specific causal effect sizes 31 with trans-ethnic genetic correlations significantly less than 1, limiting trans-ethnic 32 polygenic risk prediction. We developed a new method, S-LDXR, for stratifying 33 squared trans-ethnic genetic correlation across genomic annotations, and applied S-34 LDXR to genome-wide association summary statistics for 30 diseases and complex 35 traits in East Asians (EAS) and Europeans (EUR) (average N EAS =93K, N EUR =274K) 36 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 106 publications
1
23
0
Order By: Relevance
“…Recently developed methods for the stratified analysis of genetic correlations across ancestral populations will be invaluable for the analysis of such data. 51 Moreover, our results may have been influenced by the phenotyping and caseascertainment methods used methods used. For instance, we included data from have been influenced by the inclusion of GWAS cohorts relying primarily on self-report phenotypes, 28 though sensitivity analyses suggested minimal differences when excluding GWAS that used self-report cohorts.…”
Section: Estimating Causal Effects Of Problematic Alcohol Use On Psycmentioning
confidence: 92%
“…Recently developed methods for the stratified analysis of genetic correlations across ancestral populations will be invaluable for the analysis of such data. 51 Moreover, our results may have been influenced by the phenotyping and caseascertainment methods used methods used. For instance, we included data from have been influenced by the inclusion of GWAS cohorts relying primarily on self-report phenotypes, 28 though sensitivity analyses suggested minimal differences when excluding GWAS that used self-report cohorts.…”
Section: Estimating Causal Effects Of Problematic Alcohol Use On Psycmentioning
confidence: 92%
“…GECKO may be extended for local genetic correlation estimation based on the recent SUPERGNOVA framework by decorrelating summary statistics among local SNPs with the top principle components extracted from the local LD matrix [ 56 ]. GECKO may be extended towards trans-ethnic genetic correlation estimation based on a similar strategy used in [ 57 ]. Exploring extensions of GECKO for these additional applications may yield fruitful results in the future.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have shown 31 that heterogeneity in genetic architectures limits transferability of polygenic risk scores (PRS) across 32 populations 5, [41][42][43][44][45][46][47][48] ; critically, if applied in a clinical setting, existing PRS may exacerbate health disparities 33 among ethnic groups 49 . The population-specificity of existing PRS as well as estimates of transethnic 34 genetic correlations less than one reported in the literature 30,[50][51][52][53] indicate that (1) LD tagging and allele 35 frequencies of shared causal variants vary across populations, (2) that a sizeable number of causal variants 36 are population-specific, and/or (3) that causal effect sizes vary across populations due to, for example, 37 different gene-environment interactions. For example, due to population-specific LD, a single genetic 38 variant that is significantly associated with a trait in two populations may actually be tagging distinct 39 population-specific causal variants ( Figure 1).…”
Section: Introduction 18mentioning
confidence: 97%
“…Transethnic genetic correlation estimates (! " # ) computed from a similar set of summary statistics were obtained from a previous study 51 . Standard errors of the estimated numbers of population-specific/shared causal SNPs were computed using the last 50 iterations of the EM-MCMC algorithm.…”
mentioning
confidence: 99%